Assessment of the impact of urbanization and climate change on groundwater recharge and hydrological balance in the Turbio river watershed, Guanajuato - Orozco Medina, Ismael; Aguilera Rico, Hugo Alejandro; Martínez Bárcenas, Adrián; Pineda Capacho, Pablo Andrés (Acta Universitaria, 2022)
Assessing the potential impacts of climate change and urbanization in a hydrological system is of great importance when developing mitigation and adaptation strategies that ensure water for all sectors of the population. For this reason, this research evaluates, through projections and a distributed hydrological model, the effects of one of the most important urban areas in the state of Guanajuato on the processes of the hydrological cycle, specifically on the recharge of aquifers and the future impacts of climate change in large cities. The results show that precipitation will decrease, and with it, soil storage will be reduced mainly in urban areas. Moreover, there will be less infiltration and percolation in the system. A decrease in aquifer recharge of up to 24.9% is also forecast for the year 2035.